On the response and prediction of multi-layered flexible riser under combined load conditions. Issue 8 (7th October 2019) - Liu, Mengsha; Li, J.Y.; Chen, Lixin; Ju, J.S.
Abstract : Purpose: The internal force is more complicated in a combined load case than in a single load case, and the influence of the combined load on the stress cannot be neglected. The purpose of this paper is to study the mechanical behavior of the flexible riser under combined load conditions of tension and internal pressure or external pressure. Design/methodology/approach: The mechanical behavior of the flexible riser under combined load conditions is studied by numerical simulation with a nine-layer detailed finite element model. The layers of flexible riser are modeled separately, and the interactions between layers have been taken into consideration in numerical simulation. Findings: Under tension and internal pressure or external pressure, the pressure armor will bear extra external pressure because of the squeezing actions between layers caused by tension, and the extra external pressure will increase proportionately with the increase of the tension. Under internal pressure and tension, the internal stress for tension armor was nearly unchanged compared to that under unique tension load, whereas under external pressure and tension, the change of internal stress for tension armor was significant. Prediction methods of internal force for pressure armor and tension armor under pressure and tension are given, and the result from the formula agrees well with the simulation results. Originality/value: The prediction methods on the internal force of flexible riser proposed in this study are proven accurate, with numerical simulation results, and the prediction methods are convenient for engineering applications.